Efficacy of Integrated Approach of Yoga Therapy among Sleep-Deprived Individuals - S, Prashanth; Patil, Suchitra S; Manirathinam S; Kirthika R; S, Priyanka (International Research Journal of Ayurveda & Yoga, 2024)
Background: Sleep is crucial for brain function and is reversible. The American National Sleep Foundation recommends 7-8 hours of sleep per night. Yoga can improve sleep quality by increasing flexibility and core strength. This study aims to understand and emphasize the advantages of practicing one hour of IAYT (Integrated Approach of Yoga Therapy) for four weeks for adults and early middle-aged people suffering from sleep deprivation. Methods: A single-group pre-test post-test design, with 40 samples aged between 25 and 50 years, who met the eligibility criteria was included after obtaining informed consent. A one-hour Yoga session based on the Integrated Approach of the Yoga Therapy module was given for 4 weeks, and pre- and post-sleep quality was analyzed with the Pittsburgh Sleep Quality Index (PSQI) scale. Results: There were significant changes in all the components of PSQI values; as the sleep duration mean value reduced from 2.30 to 1.38 & p <0.000, subjective sleep quality value reduced from 2.75 to 1.80 & p <0.000, sleep latency value reduced from 2.18 to 1.43 & p <0.000 and day time dysfunction value reduced from 1.95 to 0.85 & p <0.000 among the participants. < 0.000, subjective sleep quality value reduced from 2.75 to 1.80 & p < 0.000, sleep latency value reduced from 2.18 to 1.43 & p < 0.000, and daytime dysfunction value reduced from 1.95 to 0.85 & p < 0.000 among the participants. Discussion & Conclusion: Yoga improves sleep quality by reducing latency, increasing deep sleep, reducing disruptions, and improving efficiency. This study found a significant improvement in sleep quality and quality of life after IAYT in adults who are suffering from sleep deprivation. Further research involving larger samples with controlled clinical settings is recommended.